ANALISIS PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITASBILITAS DAN RISIKO, DI PT. KIMIA HUSADA - -, Yateno (Jurnal Manajemen dan Keuangan, 2010)
The purposes of this research are know about working capital management applied, and the influence to profitability and risk. The research object in PT. Kimia Husada a trading company moves in import and distribute chemical raw material. The research user analysis descriptive method, and the hypothesis was testing by simple linier regresstion and correlation , and determination.The result for this research are working capital management at PT. Kimia Husada, applied in cash management, account receivables management, inventory management, current liablities management, account receivables management. The influence of working capital management to net working capital change since 2005 to 2008 was decreased, except in 2009 was increased.The working capital change influence to profitability (36.69%) and risk (0.240%) with Ï 22,6551. Based on t tes, the reult shows that the net working capital change influence is not significant to profitability and risk.Keyword: Working Capital, Profitability, Risk